Influence of β-Adrenergic Agonist (Metaproterenol) and Lysine on Growth, Carcass Quality in Broiler Chickens - Tahmasbi, A.M.; Kashefi, E.; Moghadam, Gh.; Taghizadeh, A.; Ghasemi, H.A. (International Journal of Poultry Science, 2006)
An investigation was made to find out the importance of β-adnergenic and lysine on carcass characteristics and blood metabolite of 648 broiler chickens from 21- 42 days of age. Effect of metaproterenol (a β2- adrenergic agonist) and lysine were assessed by mixing them in feed at 0.0, 0.25, 0.50 and 1.00 ppm metaproterenol sulfate and 100%, 115% and 130% of NRC recommended lysine in a 4x3 factorial arrangement of treatments. Chickens were reared under normal condition to 3 week of ages and then randomly allocated to treatments. Each treatment contained 3 pens with 18 birds/pen. Body weight gains (BWG), feed conversion ratio (FCR) abdominal fat pat (AFP) breast weight (BW) were measured. Result indicate that during 4th and 5th week of study using metaproterenol (0.5 ppm ), compare to control group, improved BWG (5.1%), carcass efficiency (3.4%) and breast weight (2.2%), breast and thigh muscle protein and depressed abdominal fat (P< 0.05). Increasing lysine levels lead to significant increase in body weight gain, carcass weight, carcass efficiency, breast muscle weight (P< 0.5), but it has no effect on feed intake, feed conversion ratio, blood metabolites. Data from this experiment suggested that both adding 0.5 ppm β-adrenergic agonist metaproterenol sulphate significantly improved birds performance and their carcass quality and the most efficient lysine level for broiler chickens was proved to be 115% NRC recommended.